O'Reilly artificial intelligence. (O'Reilly, 2016)
"The O'Reilly Artificial Intelligence Conference provided compelling evidence that 2016 is the year artificial intelligence moved from the province of university labs to being a critical part of the software developer's toolkit and a focus for mainstream companies. Whether you're a data scientist or software engineer looking to keep up with the latest developments; a CO in analytics, data, information, innovation or technology investigating AI trends; or a VC or corporate strategist evaluating new business opportunities, you'll find new information and insight in these videos. The compilation includes all keynotes and sessions."--Resource description page.